Package design in Japan - Rika, Tanabe (Barcelona: IndexBook)
Contiene: Numbers of entries and selected works, winning works, candidate for winning works. Grand prix and golden award winners. Winning wors. Food stuff. Confectionery. Alcoholic beverage. Soft drink. Cosmetics, perfume. Toiletry. Varieties, household commodities, clothes, medicines. Electric appliances, supplies. Wrapping papers, shopping bags, gift boxes, gifts. Cardboard containers, others. Special feature: consumers' eyes and designers' eyes. Reviews and criticism by judges
Keywords: Package